Prototype Stabilitas Kadar Air Garam Berbasis Arduino Uno (Studi Kasus : Desa Batang Kilat Medan) - Jamaludin Jamaludin; Josep Estrada Bangun (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
The salt content in pond water is one of the main factors in shrimp farming. Changes in the salt content (salinity) of water is a classic problem for shrimp farmers, because it can cause losses due to the death of shrimp resulting in crop failure. This study aims to design a prototype that functions to stabilize the salt water content in ponds, so as to prevent shrimp death. This prototype design technique is based on Arduino Uno and uses the conductivity determination method. Determination of conductivity is done by measuring the voltage. Voltage measurement is done by flowing a current with a voltage of 5 volts through an electrode that is inserted into the water. The potential difference between the ends of the electrodes is measured as the sensor input voltage. The results showed that this prototype can stabilize the salt content when the salt content in the container is unstable due to the addition of fresh water or salt water. It is hoped that this prototype can be applied to pond cultivators so that itcan be useful for preventing shrimp death.